The Role of Teachers in Addressing Learning Challenges in the Society 5.0 Era - Shilva Afriani; Selvi Yani; Heny Friantary; Wiwinda Wiwinda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the role of teachers in addressing learning challenges in the Society 5.0 era, which is characterized by the comprehensive integration of digital technology into human life. The research employs a qualitative approach using a literature study design, examining various scholarly sources such as journals, books, and relevant documents related to teachers’ roles and educational developments in the digital era. The findings indicate that teachers play a strategic role as facilitators, motivators, and innovators in the learning process. Teachers are required to integrate technology into instruction, foster creativity, and instill character values in students. In addition, teachers need to enhance their digital and pedagogical competencies to adapt to ongoing developments. Thus, the role of teachers is crucial in creating effective and relevant learning environments, enabling the development of adaptive, creative, and competitive generations in the Society 5.0 era.